EXAMINING PURCHASE INTENTION OF PRIVATE-LABEL BRANDS: THE MODERATING EFFECT OF BRAND CATEGORY - Andarini, Effly Juvita; Alversia, Yeshika (Jurnal Aplikasi Manajemen, 2023)
Private label is seen as a way to maintain profits, encourage consumption, and as a form of CSR for retail companies when empowering local small businesses. In its development, private labels have evolved into brands that pay attention to value and sustainability. A brand category in Indonesia involves SMEs as product suppliers for PLB. This study examines the influence of factors related to the store on the perception of private-label products produced by SMEs. This study collects online data from 441 Indonesian respondents who are Alfamart and Indomaret customers aged 18 or above and have shopped in the last 3 (three) months, using the non-probability sampling method with a purposive sampling technique. The collected data were tested using SEM Partial Least Squares analysis. The results reflect that store loyalty and brand image have a significant positive impact on attitudes toward buying private labels. In contrast, store loyalty and price consciousness have the least significant positive impact. On the other hand, perceived risk was was found to have a significant negative effect. The Brand Category was found to be moderating in Store Loyalty and Brand Image antecedent variables. This study is expected to be useful for academics and marketing practitioners by expanding private-label studies, especially in relation to SMEs as producers. Moreover, retailers can consider involving more SMEs in their private-label business, which will positively impact society.